AI-Based Exploratory Data Analysis - Prof. Jyoti Gaikwad,; Aniket Manohare,; Shweta Munde,; Anwar Shaikh,; Diksha Subhedar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
In today's world, where data is being generated at an unprecedented rate, organizations often struggle to make sense of the vast and complex information they collect. Extracting valuable insights from such massive datasets has become a major challenge. Traditionally, Exploratory Data Analysis (EDA) has relied on statistical techniques and manual processes. While effective, these methods can be slow, tedious, and difficult to scale when dealing with big data. This paper explores how Artificial Intelligence (AI) is transforming the way we approach EDA. By integrating AI technologies, such as Machine Learning and Deep Learning, EDA processes can be automated to a great extent — from data preprocessing and feature extraction to identifying hidden patterns and detecting anomalies. AI not only speeds up the analysis but also uncovers deeper insights that might be missed through manual exploration. Through an AI-driven EDA framework, organizations can achieve greater scalability, improve adaptability to changing datasets, and make more accurate, data-backed decisions. This paper discusses the overall structure, methodologies, tools, and techniques used in AI- powered EDA. It also highlights the real-world applications where AI-based EDA has made a significant impact — from healthcare and finance to social media analytics and business intelligence. Alongside the benefits, we also address the challenges and limitations, such as biases in automated systems and the need for human oversight. As organizations continue to generate and rely on massive volumes of data, AI-enhanced EDA offers a promising path forward, bridging the gap between raw information and actionable insights.
Keywords: AI-based EDA; Machine Learning; Deep Learning; Data Analysis; Big Data; Data Visualization; Automated Data Processing; NLP in Data Analysis